Relationship Between Instructional Design and Academic Performance in Face to Face and Blended Course of Mathematics: A Multivariate Analysis - Espinoza-Guzmán, Julia (2018)
The purpose of this investigation was to analyze the relationship of the instructional design of a face-to-face and blended Calculus and Linear Algebra (CAL) course with the performance of the students. The design of the study was quasi-experimental with a sample of 64 students of the Instituto Tecnológico de Costa Rica, which was implemented in two phases; the planning and intervention phase. The data of the instructional design variables: objectives, contents, learning activities, educational materials and evaluation strategies were collected in 2013 using a Likert scale through the self-administrated survey technique. According to the results of the t of student and the multiple linear regression, it was found that there is a statistically significant relationship between the perception of the students regarding the instructional design and their performance. These findings indicate that an adequate planning in the design of a course contributes positively in the performance of the students, either in a face-to-face or blended course. Therefore, the main recommendation is to incentivize the teachers to use the instructional design in the development of a course and to assess, as an alternative, the blended modality due to its schedule flexibility, especially when proving that the type of modality is not a significant factor in the mathematics performance.